The assassin's accomplice : Mary Surratt and the plot to kill Abraham Lincoln - Larson, Kate Clifford (Basic Books, 2008)
The true story of Mary Surratt, a shadowy figure behind the assassination of Abraham Lincoln--and the first woman executed by the federal government. Surratt, a Confederate sympathizer, ran the boarding house in Washington where the conspirators, including her rebel son, John Surratt, met to plan the assassination. When a military tribunal convicted her for her crimes and sentenced her to death, five of the nine commissioners petitioned President Andrew Johnson to show mercy on Surratt because of her sex and age. Unmoved, Johnson refused--Surratt, he said, "kept the nest that hatched the egg." Historian Larson tells the intricate story of the Lincoln conspiracy through the eyes of its only female participant. Based on long-lost interviews, confessions, and court testimony, the text explores how Mary's actions defied nineteenth-century norms of femininity, piety, and motherhood, leaving her vulnerable to a punishment historically reserved for men.--From publisher description